Integrative linkage and recombination analysis of 25 X-STRs across 7 linkage groups using pedigree-based and SNP-based strategies - Qian, Jinglei; Qian, Xiaoqin; Ji, Qiqi; Li, Zhimin; Shao, Chengchen; Xu, Hongmei; Yang, Fan; Xie, Jianhui (Frontiers in Genetics, 2025)
IntroductionX-chromosomal short tandem repeats (X-STRs) are valuable genetic markers in forensic science for resolving complex kinship scenarios. However, the linkage relationship and recombination of X-STRs remain poorly characterized.MethodsBased on high-density SNP data with relatively low mutation rates, we developed a pedigree-based method to analyze the recombination relationships between these X-STR linkage groups (LGs). We used X-STRs data from 66 two-generation families and X-SNPs data from 602 X-chromosomal SNP trios from the 1000 Genomes Project. We investigated the linkage relationships among 25 X-STR loci, grouped into seven LGs, including three identified regions (Xp21.1, Xq21.31, Xq23) and four Argus X-12 (Xp22.2, Xq12, Xq26, Xq28), provided broader coverage linkage groups of X-STR.ResultsWe found strong intra-group linkage (Maximum logarithm of odds (MLOD) > 5) and near independence between groups (MLOD <1). Estimated recombination rates of X-STR data ranged from 0.0000 to 0.0487 within LGs, and from 0.1561 to 0.4133 between LGs, while the recombination fraction between the 7 linkage groups occurred in approximately 50% of informative meioses. LD decay analysis showed that R2 dropped to 0.1 at a distance of approximately 3.7 kb, supporting the feasibility of using SNP-derived LD signals to infer STR recombination patterns at fine scale.DiscussionThe family-based methods with X-SNP provide a more robust framework for evaluating X-STR linkage with the advantage of a relatively low mutation rate, high density and phased, particularly for newly developed loci lacking extensive haplotype databases.ConclusionThese findings contribute to a more precise understanding of X-STR inheritance and enhance their reliability in forensic kinship analysis.